HOST STRAIN IDENTIFICATION OF Spodoptera frugiperda (J.E. SMITH) FROM SERIAN AND KOTA SAMARAHAN, SARAWAK, MALAYSIA - Chen Wah, Kueh; Najwa, Hamsein; Jisia, Jimbau; Freddy Yeo, Kuok San (Faculty of Science and Technology (FST), UKM, 2023)
Spodoptera frugiperda (J.E. Smith) is one of the most invasive pests around the world, causing significant economic losses to corn and rice farmers. In September 2019, the Department of Agriculture (DOA), Sarawak, Malaysia has confirmed the presence of S. frugiperda in corn fields of Kuching, Sarawak. This study aimed to identify the host strain of 15 S. frugiperda isolates from Serian and Kota Samarahan, Sarawak, using the mitochondrial cytochrome oxidase subunit 1 (CO1) gene marker. Based on the CO1 sequence, corn and rice strain of S. frugiperda were identified among the 15 S. frugiperda isolates. Based on the migration pattern of S. frugiperda, it appears that only corn strain migrated to Asian countries; thus, this study proposes that interstrain hybrid may be presence in corn fields of Serian and Kota Samarahan. CO1 gene alone is ineffective to identify the host strain of S. frugiperda. Therefore, further study should include the nuclear sex-linked triosephosphate isomerase (TPI) gene sequence in addition to CO1 gene sequence for more conclusive host strain identification of S. frugiperda.